2022
DOI: 10.1109/lra.2022.3190087
|View full text |Cite
|
Sign up to set email alerts
|

Visibility-Aware Navigation With Batch Projection Augmented Cross-Entropy Method Over a Learned Occlusion Cost

Abstract: We present two real-time trajectory optimizers based on the Cross-Entropy Method for visibility-aware navigation. The two approaches differ in handling inequality constraints stemming from bounds on motion derivatives, collision avoidance, tracking error, etc. Our first optimizer augments the inequalities into the cost function, while the second one relies on a novel GPU accelerated batch projection algorithm. We adopt a learningbased approach to ensure a fast query of the occlusion cost arising from the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In contrast, increasing the covariance of control perturbation has been shown to make MPPI diverge [11]. Improvement over Author's Prior Work [15] PRIEST builds on our prior work [15] that used projection-augmented sampling for visibility-aware navigation. Our current work targets a much broader scope of navigation problems with potentially non-smooth costs.…”
Section: Decenteralized Priest (D-priest)mentioning
confidence: 99%
“…In contrast, increasing the covariance of control perturbation has been shown to make MPPI diverge [11]. Improvement over Author's Prior Work [15] PRIEST builds on our prior work [15] that used projection-augmented sampling for visibility-aware navigation. Our current work targets a much broader scope of navigation problems with potentially non-smooth costs.…”
Section: Decenteralized Priest (D-priest)mentioning
confidence: 99%
“…Robotont is being continuously validated as an educational tool and a research platform - notable examples of such results have already been reported in a number of research publications [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . More specifically, this robot has been extensively used to deliver university teaching, professional training, and online courses on the topics of ROS and robotics as described in [20] , [21] , [22] , [23] .…”
Section: Validation and Characterizationmentioning
confidence: 99%
“…[28] , [29] , [30] , [31] , [32] ) and a platform to validate cutting-edge robotics research about e.g. software frameworks [24] and motion-planning [25] , [26] , [27] .…”
Section: Validation and Characterizationmentioning
confidence: 99%
“…In [19], the UAV shared its voxel map of the environment with a UGV, which converted the voxel map to an elevation map and utilized it for path planning. In [20], a trajectory optimization approach for a UGV guiding a UAV while maintaining visibility was proposed, motivated by scanning warehouse racks for inventory management.…”
Section: B Related Workmentioning
confidence: 99%